AB0033 Intracellular Expression of Survivin and Bcl-6 is Decreased in CD4+ T-Cells of Rheumatoid Arthritis Patients with High Serum Survivin. (10th June 2014) - Turkkila, M.; Filluelo Cavallini, N.; Töyrä Silfverswärd, S.; Erlandsson, M.; Brisslert, M.; Pullerits, R.; Andersson, K.; Bokarewa, M.
Abstract : Background: Survivin is recognized as a marker of persistently active and erosive RA. The findings in experimental arthritis suggested that survivin co-ordinates the antigen-dependent leukocyte maturation and function by regulating transcriptional activity of Bcl-6, essential factor of germinal center formation and a factor involved neoplastic transformation to lymphoma. Objectives: We studied intracellular expression of survivin and Bcl-6 in the peripheral lymphocytes and its relation to clinical features and treatment of RA patients. Methods: The intracellular expression of survivin and Bcl-6 was studied on the effector and memory subsets of CD4+ and CD8+ T-cells and in CD19+ B-cells in 18 RA patients using flow cytometry. Serum and mRNA levels of survivin were analysed in 144 RA patients (age 21-71 years, disease duration 1-49 years) using ELISA and qPCR, respectively. Patients with serum levels of survivin >0.45 ng/mL comprised the serum survivin-positive (sSurv+) group. Results: The sSurv+ group (n=76) was characterized by higher frequency of RF+ and aCCP+ patients, as well as by higher levels of aCCP and of differentiation factor Flt3-ligand compared to sSurv – (n=68). The sSurv+ and sSurv- patients were similar with respect to age, disease duration, DAS28 and anti-rheumatic treatment. Intracellular mRNA levels of Bcl-6 were lower in sSurv + compared to sSurv – patients, while RNA of survivin were similar. Flow cytometry showed that survivin was present in >85% of non-stimulated T-cells and B-cells lymphocytes of RA patients. The survivin hi subset comprised 2-14% of T-cells and was enriched in the effector (CD62L neg ) population of CD4+ T-cells compared to central memory and naïve CD4+ T-cells. The expression of Bcl-6 was found within 7-38% of survivin + effector CD4+ T-cells and in 21-69% of CD19+ B-cells. The subsets of survivin+ and of survivin+Bcl-6+ T-cells was smaller in the sSurv+ patients compared to sSurv – patients, and was inversely correlated to the levels of serum survivin in these patients. The subset of survivin+Bcl-6+ B-cells was similar in sSurv+ and sSurv- patients. Conclusions: In this pilot study we demonstrate that RA patients have co-expression of the two oncoproteins involved in neoplastic transformation to lymphoma, survivin and Bcl-6. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5490